2012
DOI: 10.1155/2012/536396
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Lipoprotein Cholesterol Levels in Plasmodium berghei Malarial Infection by Crude Aqueous Extract of Ganoderma lucidum

Abstract: In this study, attempt is made to establish changes in serum and liver lipoprotein cholesterols accompanying Plasmodium berghei malarial infection in mice treated with aqueous extract of Ganoderma lucidum at 100, 250, and 500 mg/kg body weight in comparison with 15 mg/kg chloroquine (CQ). Significant increases in all the lipoprotein fractions were observed in infected untreated mice compared with normal control mice. Treatment with 100 and 250 mg/kg G. lucidum extract produced significant reduction in serum to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
1
17
0
3
Order By: Relevance
“…It is envisaged that some valuable nutrients may have leached out at any of these processing stages (Akindahunsi et al, ). While low protein and ash contents of food may not be desirable due to their contributions to cellular growth and development and maintenance of healthy living, reduced fat level of food is noteworthy as foods with low‐fat content is usually recommended for diabetes and persons at high risk for cardiovascular diseases (CVD) (Oluba, Olusola, Eidangbe, Babatola, & Onyeneke, ). The percentage amylose fraction in the starch content for both white and yellow gari samples used in this study was high compared to the range of values (19.5–22.4%) obtained for five different cassava cultivars by Charles, Chang, Ko, Sriroth, and Huang () and the observed amylose: amylopectin ratio were far higher than the values reported for cassava by Nwokocha, Aviara, Senan, and Williams ().…”
Section: Discussionmentioning
confidence: 99%
“…It is envisaged that some valuable nutrients may have leached out at any of these processing stages (Akindahunsi et al, ). While low protein and ash contents of food may not be desirable due to their contributions to cellular growth and development and maintenance of healthy living, reduced fat level of food is noteworthy as foods with low‐fat content is usually recommended for diabetes and persons at high risk for cardiovascular diseases (CVD) (Oluba, Olusola, Eidangbe, Babatola, & Onyeneke, ). The percentage amylose fraction in the starch content for both white and yellow gari samples used in this study was high compared to the range of values (19.5–22.4%) obtained for five different cassava cultivars by Charles, Chang, Ko, Sriroth, and Huang () and the observed amylose: amylopectin ratio were far higher than the values reported for cassava by Nwokocha, Aviara, Senan, and Williams ().…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in total cholesterol level could also be contributedin reduction of the mean levels of LDL-C and HDL-C in same patient. The positive relationship between total cholesterol, LDL-C and HDL-C has been widely reported even in normal individuals [14]. The reason for the low triglyceride level in infected subjects is unclear but Sturrock et al [15] had demonstrated that S. mansoni is capable to obtain phospholipids and triglyceride from the host.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using mouse models, for example, have demonstrated the hypoglycaemic (Xiao et al. 2012) and LDL-cholesterol lowering (Oluba et al. 2012) effects of Ganoderma extracts.…”
Section: Medicinal Basidiomycetesmentioning
confidence: 99%